(untitled) (LEARNing Landscapes, 2009)
What literacy means has evolved significantly in recent decades, but even in the context of Quebec, where the provincial curriculum embraces a forward-thinking definition of literacy, multiple understandings of literacy and reading coexist within the same community. This article argues that how the concepts of reading and literacy are understood, and how best to teach them, continues to be framed within the boundaries set out by traditionally opposing research paradigms, and that these frameworks have further complicated the challenge of helping students become strong readers of print. With a specific focus on the reading of print, this article examines how these understandings differ and what this has meant for reading and literacy instruction. It is argued that a rethinking of the way that research informs pedagogy may further the benefits that the researcher-practitioner relationship brings to classroom practice.